2014
DOI: 10.1016/j.enpol.2013.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Securitization of residential solar photovoltaic assets: Costs, risks and uncertainty

Abstract: Limited access to low-cost financing is an impediment to high-velocity technological diffusion and high grid penetration of solar photovoltaic (PV) technology. Securitization of solar assets provides a potential solution to this problem. This paper assesses the viability of solar asset-backed securities (ABS) as a lower cost financing mechanism and identifies policies that could facilitate implementation of securitization. First, traditional solar financing is examined to provide a baseline for cost comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 22 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…This same open source disclosure of the testing results will also be adhered to for the hardware designs themselves following an open-source hardware methodology (Buitenhuis and Pearce, 2012). This system will need to compared to the other new low-weight commercial rooftop racking systems Holton, 2014) and an up-to-date economic analysis including financing will need to be performed (Singh and Singh, 2010;Talavera et al, 2010;Branker et al, 2011a,b;Bazilian et al, 2013;Swift, 2013;Alafita and Pearce, 2014;Ondraczek et al, 2015). In addition to evaluating the effectiveness of the X-wire system with commercial rooftops, the system could also be applicable in rural areas and developing countries where electricity is either very expensive or non-existent, where rapid prototypers (King et al, 2014) could be used for the manufacture of the racking systems and could further be powered by the PV of which it manufactured.…”
Section: Discussionmentioning
confidence: 99%
“…This same open source disclosure of the testing results will also be adhered to for the hardware designs themselves following an open-source hardware methodology (Buitenhuis and Pearce, 2012). This system will need to compared to the other new low-weight commercial rooftop racking systems Holton, 2014) and an up-to-date economic analysis including financing will need to be performed (Singh and Singh, 2010;Talavera et al, 2010;Branker et al, 2011a,b;Bazilian et al, 2013;Swift, 2013;Alafita and Pearce, 2014;Ondraczek et al, 2015). In addition to evaluating the effectiveness of the X-wire system with commercial rooftops, the system could also be applicable in rural areas and developing countries where electricity is either very expensive or non-existent, where rapid prototypers (King et al, 2014) could be used for the manufacture of the racking systems and could further be powered by the PV of which it manufactured.…”
Section: Discussionmentioning
confidence: 99%
“…Although some writers mention the solar TPO business model (e.g., Alafita and Pearce, 2014;Friebe et al, 2013;Huijben and Verbong, 2013) and analyze its value for consumers (e.g., Davidson et al, 2015;Kulatilaka et al, 2014;Liu et al, 2014;Rai and Sigrin, 2013), no analysis of the model from the perspective of TPO providers and with a focus on policy actions has been carried out to the knowledge of this author. Drury et al (2012) suggested the value of enabling policies for solar TPO in the quote above but provided few policy suggestions.…”
Section: Introductionmentioning
confidence: 98%
“…The emerging financial instrument could be a promising vehicle for solar city strategies: incorporating public debt in the financing structure offers attractive benefits such as improvements in financing terms, risk mitigation, and access to a broader capital pool . Overall, such strategies could achieve a lower cost of capital, less risk, and reduce project costs . It is estimated that a reduction in the levelized cost of energy (LCOE) of 8–16% occurs when a portion of a project or portfolio's typical capital stack is replaced with public capital vehicles …”
Section: Introductionmentioning
confidence: 99%